The spiritual crisis of man: Christian speech’s by Søren Kierkegaard - Pavlíková, Martina; Králik, Roman (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2015)
In the article, the authors analyze and interpret Kierkegaard's work "The Spiritual Crisis of Man: Christian Conversations." Researchers focus on understanding a person and their interests. The authors rethink Kierkegaard's saying that everyone must choose between the aesthetic and religious stages of life.